(untitled) (Construction Economics and Building, 2014)
Philip Davenport and Helen Durham, 2013, Federation Press, 3rd ed, ppi-xiv, 1-338, index, case table, legislation table, glossary of terms, ISBN978-1-86287-912-6, Price AUD85.00